A Cyanide‐Free Synthesis of Acylcyanides through Ru‐Catalyzed C(sp3)‐H‐Oxidation of Benzylic Nitriles. Issue 6 (25th April 2019) - Eisele, Pascal; Bauder, Michael; Hsu, Shih‐Fan; Plietker, Bernd
Abstract: A practical method for generation of acylcyanides devoid of any external cyanide sources is presented that relies on a mild Ru‐catalyzed selective C−H‐oxidation of benzylic nitriles. The starting materials are smoothly generated through condensation of the corresponding carboxylic acid amides using silanes. The obtained acylcyanides can be employed in a plethora of transformation as exemplified to some larger extend in the sequence of C−H‐oxidation‐Tischenko‐rearrangement for the generation of structurally diverse benzoyloxycyanohydrines. Abstract : Three on one strike : The Ru‐catalyzed C−H‐oxidation of benzylnitrile derivatives provides access toward reactive acylcyanides which can be transformed in‐situ into esters, amides, but also into acylcyanohydrines. Upon coupling the process to a fluoride‐catalyzed dehydrogenation of carboxylic acid amides allows for a three‐step, one‐pot preparation of acylcyanohydrines without the need to employ cyanide salts.